Membership in a breast cancer peer-support organization (Amazons Club) and depression - Kozela, Magdalena; Stepaniak, Urszula; Pająk, Andrzej (Contemporary Oncology/Współczesna Onkologia, 2011)
Background : Mastectomy, a procedure carried out to save life in women with breast cancer, is a huge burden as a result of the feeling of lethal threat, mutilation and anxiety of social exclusion. The objective was to assess the level of depression in members and non-members of the Amazons Club (AC), to assess the relationship between level of depression and membership in AC, and to assess the importance of benefits for AC members. Material and methods : The study included 101 women (50 members and 51 non-members of the AC), who were interviewed using a structured questionnaire. Depression was measured using the Center for Epidemiological Studies Depression Scale (CES-D). Results : 78% of AC members highly assessed the benefits (psychological support, access to expertise, social meetings) of membership in this organization. The proportion of depression was lower among women belonging to the AC (14 vs. 36%, p < 0.05). A significant difference in the average level of depression was observed and it was lower among women belonging to the AC (9.6) than women not belonging to the AC (14.3) (p < 0.05). Membership in the AC was not significantly associated with a reduction in the level of depressive symptoms in the entire group, after adjustment for covariates. Conclusions : Despite the very positive assessment of membership and broad participation in the activities offered by the AC, there was no significant association between membership in the AC and the level of depression in women after mastectomy.